1986
DOI: 10.1007/bf00743010
|View full text |Cite
|
Sign up to set email alerts
|

The random collision model and a critical assessment of diffusion and collision in mitochondrial electron transport

Abstract: This review focuses on our studies over the past ten years which reveal that the mitochondrial inner membrane is a fluid-state rather than a solid-state membrane and that all membrane proteins and redox components which catalyze electron transport and ATP synthesis are in constant and independent diffusional motion. The studies reviewed represent the experimental basis for the random collision model of electron transport. We present five fundamental postulates upon which the random collision model of mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
242
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(253 citation statements)
references
References 72 publications
10
242
0
1
Order By: Relevance
“…NADH: ferricyanide oxidoreductase activity was determined following oxidation of NADH at 340 nm (3 NADH ¼ 6.22 mM À1 cm À1 ) in a reaction buffer containing 100 mM MOPS pH 7.2, 250 mM NADH and 250 mM K 3 [Fe(CN) 6 ] [40]. Succinate:DCPIP oxidoreductase activity was monitored by following the PMS-coupled reduction of DCPIP at 578 nm at 37 C (3 DCPIP ¼ 20.5 mM À1 cm À1 ).…”
Section: Catalytic Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…NADH: ferricyanide oxidoreductase activity was determined following oxidation of NADH at 340 nm (3 NADH ¼ 6.22 mM À1 cm À1 ) in a reaction buffer containing 100 mM MOPS pH 7.2, 250 mM NADH and 250 mM K 3 [Fe(CN) 6 ] [40]. Succinate:DCPIP oxidoreductase activity was monitored by following the PMS-coupled reduction of DCPIP at 578 nm at 37 C (3 DCPIP ¼ 20.5 mM À1 cm À1 ).…”
Section: Catalytic Activitiesmentioning
confidence: 99%
“…The resolved gradient was divided in 1 mL fractions (F1eF9 from highest to lowest molecular mass, respectively) and the respiratory chain activities with artificial electron acceptors, the oxygen consumption rates and heme b content were determined. NADH:K 3 [Fe(CN) 6 ] oxidoreductase activity was present throughout the gradient fractions being maximal in fraction 1. Such distribution may be explained by the presence of type I and II NADH:quinone oxidoreductases as monomers, homodimers or combined with other respiratory chain complexes in supercomplexes.…”
Section: Sucrose Gradient Analysis Of E Coli Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies by Hackenbrock and colleagues of the diffusion properties of the different actors of the respiratory chain, in particular of cytochrome c, brought compelling evidences for a random collision model (reviewed in ref. 8). Rich reviewed these issues and listed four different models ranging from "liquid" to "solid" state, the intermediate cases comprising the partial association of the individual components, or "patches" containing higher concentration of one or more cofactors (9).…”
mentioning
confidence: 99%
“…1). Another major reason was the pioneering work of Hackenbrock and co-workers (2,3) who demonstrated that the concentration of free-diffusing components in the inner mitochondrial membrane and the collision rate between them is enough to explain the observed respiratory rates in mitochondria.…”
mentioning
confidence: 99%